1991
DOI: 10.1136/thx.46.7.499
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide and terbutaline or terbutaline alone in children with mild asthma: effects on bronchial hyperresponsiveness and diurnal variation in peak flow.

Abstract: The effects of treatment with budesonide (200 pg twice daily) and terbutaline (500 pg four times daily) has been compared with the effects of placebo and terbutaline in 27 children with mild asthma, aged 7-14 years, in a double blind, randomised placebo controlled study over eight weeks. Bronchial responsiveness (PC20 histamine), lung function, the amplitude of diurnal variation in peak expiratory flow (PEF), and symptom scores were measured. Baseline FEV, was over 70% predicted and PC20 histamine less than 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
2

Year Published

1993
1993
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 27 publications
0
17
2
Order By: Relevance
“…WAALKENS et al [19] compared the effects of treatment with budesonide 200 µg twice daily and terbutaline with the effects of terbutaline alone in a placebo-controlled, double-blind study in 27 children with mild asthma (FEV1 93% pred) over 8 weeks. They found that mean FEV1 did not change in either group and that there was no significant change in morning PEF, although they found a significant difference in favour of BUD for evening and nocturnal PEF.…”
Section: Discussionmentioning
confidence: 99%
“…WAALKENS et al [19] compared the effects of treatment with budesonide 200 µg twice daily and terbutaline with the effects of terbutaline alone in a placebo-controlled, double-blind study in 27 children with mild asthma (FEV1 93% pred) over 8 weeks. They found that mean FEV1 did not change in either group and that there was no significant change in morning PEF, although they found a significant difference in favour of BUD for evening and nocturnal PEF.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore these effects were maintained over the 24 months of follow-up ( Figure 3). In a smaller study of 27 asthmatic children, the combination of budesonide (400 jg daily) and terbutaline (2000 jg daily) produced a reduction in histamine reactivity with a 2.1 doubling dose difference compared with terbutaline plus placebo [25]. [40,41].…”
Section: The Influence Of Disease Modifying Therapymentioning
confidence: 99%
“…Until now only a few studies have evaluated the effect of ICS in children with mild asthma [9][10][11][12][13]. Most of these studies were performed in older children and using different effect parameters.…”
Section: Discussionmentioning
confidence: 99%
“…There have only been a few studies concerning the short- [9,10] or long-term effects [11] of ICS in children with mild asthma. Placebo controlled studies are especially rare [12][13][14].…”
mentioning
confidence: 99%